A relação estabelecida por aprendizes de línguas com séries de televisão: interfaces com a sala de aula e com o processo de aprendizagem de inglês - Toledo, Fabiano Bernardes de (2018)
The focus of this work is on the contact of English language learners with cultural products (TV series) in English outside the classroom, and possible interfaces with the formal learning of this language. In this sense, we analyze some aspects involved in such contact, such as the use (or not) of learning strategies, the influence of the teacher in the use of these strategies, and attention to linguistic forms. The methodology of the research involves questionnaires, interviews, field notes, and audio recordings of classes taught by the teacher-researcher at a federal technological university in Brazil. Our main focus is on TV series, as they represent one of the cultural products in English with which students have the most contact nowadays (SOCKETT, 2014, p. 34), and because research shows that watching them frequently can benefit the acquisition of this language (RICHARDS, 2015; SOCKETT, 2014; WANG, 2012). We verified that the development of activities whose procedures involved, among other aspects, repeated and continuous contacts with series (chosen by the students), followed by discussions about the episodes watched, provided students with the opportunity to develop interest in this kind of cultural product, resulting in increased contact with it outside the class. In addition, we found that the presentation and discussion, in class, of studies showing benefits that the contact with series can bring, in terms of learning, and strategies that can be used to enhance such benefits, followed by activities in which attention to linguistic and cultural aspects of the series was required, helped learners to a) perceive the potential of series as an English learning tool, and b) reflect on the use of strategies, undertaking changes that resulted in increased learning. In this way, we were able to conclude that the English class, besides representing a place where more traditional teaching practices are carried out, can also be a place where students may develop interest in a cultural product in English, and in which guidance can be provided so that the resulting increase in exposure to the target language outside the classroom becomes potentially more profitable in terms of language acquisition.